Changes in cranial CSF volume during hypercapnia and hypocapnia. Issue 2 (February 1989) - Grant, R; Condon, B; Patterson, J; Wyper, D J; Hadley, M D; Teasdale, G M
Abstract : Magnetic resonance imaging was used to measure the effect of inhalation of 7% CO2 and hyperventilation with 60% O2 on human cranial cerebrospinal fluid volume. During CO2 inhalation there was a reduction in the cranial CSF volume ranging from 0.7-23.7 ml (mean 9.36 ml). The degree of reduction in cranial CSF volume was independent of the individual subject's increase in end-expiratory pCO2 or mean arterial blood pressure, in response to hypercapnia. During hyperventilation with high concentration oxygen the cranial CSF volume increased in all subjects (range 0.7-26.7 ml, mean 12.7 ml). The mean changes in cranial CSF volume, induced by hypercapnia and hypocapnia, were very similar to the expected reciprocal changes in cerebral blood volume.